2011
DOI: 10.1186/1471-230x-11-86
|View full text |Cite
|
Sign up to set email alerts
|

Appointment waiting times and education level influence the quality of bowel preparation in adult patients undergoing colonoscopy

Abstract: BackgroundRisk factors for poor bowel preparation are recognized to be independent of the type of bowel preparation method used. Patient and administrative factors influencing bowel preparation are known to vary in different healthcare systems.MethodsA prospective, cross-sectional study of patients undergoing colonoscopy in an Asian tertiary centre was conducted to identify risk factors associated with poor bowel preparation, and to evaluate the impact of poor bowel preparation on technical performance and pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
123
3
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(138 citation statements)
references
References 20 publications
7
123
3
5
Order By: Relevance
“…In a retrospective United States study of 300 patients, univariate analysis demonstrated that a mean age of ≥ 66 years was predictive of poor colonoscopy preparation [60] . In two recent Asian studies, age ≥ 60 years were similarly associated with a poor bowel preparation [27,54] . An increased age is known to be associated with a reduced colonic transit, greater co-morbidity and polypharmacy, all of which are known to impact on colonic cleansing [39,[61][62][63][64] .…”
Section: Agementioning
confidence: 95%
See 2 more Smart Citations
“…In a retrospective United States study of 300 patients, univariate analysis demonstrated that a mean age of ≥ 66 years was predictive of poor colonoscopy preparation [60] . In two recent Asian studies, age ≥ 60 years were similarly associated with a poor bowel preparation [27,54] . An increased age is known to be associated with a reduced colonic transit, greater co-morbidity and polypharmacy, all of which are known to impact on colonic cleansing [39,[61][62][63][64] .…”
Section: Agementioning
confidence: 95%
“…Studies in both the West [65,66] and the East [67] have demonstrated that male gender is an independent predictor of poor bowel preparation. Among 649 American patients, of whom 21.7% had poor bowel preparation, Ness et al [65] reported that male gender was an independent predictor of poor bowel preparation among other patient-related factors.…”
Section: Gendermentioning
confidence: 99%
See 1 more Smart Citation
“…First, it did not assess patients' socioeconomic status or education level, which are also potential factors affecting the quality of bowel preparation (10,11,24). Second, since we evaluated bowel preparation for afternoon colonoscopy, these results may not apply to morning colonoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported risk factors associated with inadequate bowel preparation (5-9); however, the relationship between the waiting time from education to colonoscopy and risk of inadequate bowel preparation has not been studied in detail. Chan et al (10) reported that appointment waiting times influenced the quality of bowel preparation, and a prolonged appointment waiting time of >16 weeks was associated with poor bowel cleansing (odds ratio: 1.86, P=.035). Another retrospective study (11) in the United States did not identify waiting time as a risk factor for poor bowel cleansing, but in this study the mean waiting time was 4.3 weeks.…”
Section: Introductionmentioning
confidence: 99%